The international law of disaster relief - Caron, David D; Kelly, Michael J & Telesetsky, Anastasia (Cambridge University Press, 2014)
"This edited volume analyzes the evolution of international disaster law as a field that encompasses new ideas about human rights, sovereignty, and technology"--